2013
DOI: 10.13107/jocr.2250-0685.114
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Median Nerve Neuroma in Wrist. A Case Report and brief review of Literature

Abstract: Introduction:Distal median nerve masses may be developed post-traumatic or non-traumatic. In this paper, we aim to present a 52 year old female case with a postraumatic neuroma of the median nerve in the left wrist.Case Series:A 52-year-old female patient had accidental incised wound over her left wrist which was primarily sutured. She presented 6 months later with unrelieved pain and growing swelling at the wrist. USG showed solid mass of size 2x3 cms. Intraoperatively the mass was seen to arise from medial n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Neurolysis, secondary end-to-end suture repair, and graft repair were the methods studied, and they concluded that in case of absent sensory or motor function or loss of compound action potentials across the nerve, the use of short nerve autografts < 5cm presented the best outcomes regarding the motor and sensory function of the nerve. In cases of preserved function, however, neurolysis accompanied by other procedures shows favorable results [ 6 - 7 , 13 ]. Elliot D et al [ 13 ] supported the use of neurolysis followed, however by wrapping the nerves in vascularized forearm fascia for the elimination of neuropathic pain, which originates from the median or ulnar nerve and is caused by direct injury, with or without repair, or scar formation because of injury to adjacent structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurolysis, secondary end-to-end suture repair, and graft repair were the methods studied, and they concluded that in case of absent sensory or motor function or loss of compound action potentials across the nerve, the use of short nerve autografts < 5cm presented the best outcomes regarding the motor and sensory function of the nerve. In cases of preserved function, however, neurolysis accompanied by other procedures shows favorable results [ 6 - 7 , 13 ]. Elliot D et al [ 13 ] supported the use of neurolysis followed, however by wrapping the nerves in vascularized forearm fascia for the elimination of neuropathic pain, which originates from the median or ulnar nerve and is caused by direct injury, with or without repair, or scar formation because of injury to adjacent structures.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic median nerve neuroma in-continuity was the diagnosis, and dissection followed by neurolysis and nerve wrapping was performed. Another case of a post-traumatic neuroma of the median nerve, which was separated from the surrounding scar tissue and then excised, was reported by Aslan et al [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a consequence of a nerve-mending process which could affect any part of the body after external trauma or surgery. It is not classified as a neoplastic process but a disorganized proliferation of nerve axons, Schwann cells, and perineural fibroblasts following Wallerian nerve degeneration [2]. Ultra-high-frequency ultrasound (UHFUS) is a new technology in clinical diagnostic imaging.…”
Section: Introductionmentioning
confidence: 99%